Reflection of the Sea-Born Horse’s Mythologem in the Armenian Fairy-Tales and Epic - Dalalyan, Tork (Bulletin of Yerevan University B: Philology, 2022)
Since ancient times, the sea and water were considered as symbols of the origin and permanence of life, therefore according to popular beliefs a marine/aquatic origin was attributed to many mythical animals and beings. In this sense, mythical steeds were not an exception. In this paper we try to explore, through the data of Armenian epic folklore, the sea-born mythical steed’s motif, in which the worships of the sun, horse, and water/sea are interwoven. While in some epic genres of folklore it is expressed as a motif, from the point of view of comparative mythology it can be studied as an archaic mythologem, which’s antiquity reaches at least as far back as the domestication of the wild horse.
Keywords: see; horse; sun; down; sunset; twinse; foremother